Dámaris Romero-González, Israel Muñoz-Gallarte y Gabriel Laguna-Mariscal (eds.), Visitors from beyond the Grave. Ghosts in World Literature. - Pino Alonso, David (Revista de Estudios Latinos, 2021)
Dámaris Romero-González, Israel Muñoz-Gallarte y Gabriel Laguna-Mariscal (eds.), Visitors from beyond the Grave. Ghosts in World Literature. (Série Humanitas Suplementum - Estudios Monográficos) Coimbra, Universidade de Coimbra, 2019. 300 pp. ISBN 978-989-26-1763-3; e-ISBN 978-989-26- 1765-7.